Parental Leave, Worker Substitutability, and Firms' Employment - Mathias Huebener; Jonas Jessen; Daniel Kühnle; Michael Oberfichtner (Institute of Labor Economics (IZA), 2024)
Motherhood and parental leave are frequent causes of worker absences and employment interruptions, yet we know little about their effects on firms. Based on linked employer-employee data from Germany, we examine how parental leave absences affect small- and medium-sized firms. We show that they anticipate the absence with replacement hirings in the six months before childbirth. A 2007 parental leave reform extending leave absences reduces firm-level employment and total wages in the first year after childbirth, driven by firms with few internal substitutes for the absent mother. However, we do not find longer-term effects on firms' employment, wage-bill, or likelihood to shut down. We find that the reform increases replacement hirings, but firms directly affected do not respond to longer expected absences of mothers by subsequently hiring fewer young women. Overall, our findings show that extended parental leave does not have a lasting impact on firms when these can anticipate the absences.
Keywords: J16; J18; J24; 330; parental leave; worker absences; worker substitutability